IDENTIFICATION OF SCCMEC TYPE IN ISOLATE OF METHICILLIN RESISTANT Staphylococcus aureus (MRSA) IN JAMBI BY USING POLYMERASE CHAIN REACTION (PCR) - Humaryanto, Humaryanto; Hanina, Hanina; Lipinwati, Lipinwati; Simanjuntak, Charles Apul (Indonesian Journal of Tropical and Infectious Disease, 2020)
Staphylococcal cassette chromosome mec (SCCmec) is one of the mobile genetic elements of Methicillin-Resistant Staphylococcus aureus (MRSA) that carries many resistance genes and allows SCCmec to move from one bacterium to another. Twelve types of SCCmec have been identified throughout the world. Identification of SCCmec type is needed to determine the pattern of MRSA resistance in a particular region. This study aimed to identify the type of SCCmec MRSA from clinical samples. Specifically, this study was conducted at the Biomolecular Laboratory of the Faculty of Medicine and Health Sciences of Jambi University in June 2018-February 2019. Culture was carried out on 100 clinical specimens of festering wound swabs from inpatients at hopitals in Jambi City. A total of 32 samples of Staphytect plus test positive were tested using Cefoxitin disc diffusion method and MecA Polymerase Chain Reaction (PCR). There were 14 samples identified as MRSA isolates, namely twelve samples (85.72%) of SCCmec type III, one sample (7.14%) of SCCmec type II, and one sample (7.14%) of SCCmec type IVb. The results were different from previous studies where all MRSA isolates (100%) in Indonesia were SCCmec type III, although most SCCmec types were still dominated by SCCmec type III. This study concludes that there has been a shift in the content of SCCmec in MRSA isolate originating from hospitals in Jambi city.